Asylum seekers' perceptions of the responsiveness of care: a qualitative study in Germany. (20th October 2021) - Ziegler, S; Biddle, L; Bozorgmehr, K
Abstract: Background: Research on healthcare for asylum seekers and refugees (ASR) has focused strongly on accessibility and legal entitlements, with quality of care receiving little attention. This study aimed to assess responsiveness - the non-medical quality of care - as perceived by recently arrived ASR in Germany. Methods: 31 ASR with existing medical conditions were recruited in six refugee clinics and three psychosocial counselling centres. Semi-structured, qualitative interviews were conducted, reconstructing the patient journeys after arrival. Interviews were recorded, transcribed and analysed thematically. Results: Responsive care is important in evaluations of the German health system. Trust in providers and their expertise as well as accounts of a "caring" attitude, respectful treatment - e.g. taking afflictions and the situation of ASR seriously - and clear communication resurfaced frequently in ASR narratives. Their evaluation of care was affected by related expectations being exceeded or disappointed. Other responsiveness dimensions, like cleanliness of facilities, autonomy of decision-making and choice of provider were mentioned seldom. Participants voiced a high overall satisfaction with German healthcare. We observed that positive experiences were often set in contrast to negative experiences in countries of origin or during transit and many participants evaluated their healthcare experience initially in terms of the perceived technical quality and outcome of care rather than referring to responsiveness. Conclusions: Aspects of respectful treatment, clear communication and trust are important to ASR. To further strengthen the provision of high quality and responsive care to a diverse patient population, policy action is needed: expansion of professional interpreting services, provision of professional training to increase the reflective and structural competence of healthcare staff and alignment between the healthcare and asylum processes to promote continuity of care. Key messages: Health systems need to pay attention to the responsiveness dimensions deemed important by asylum seekers to better address needs and concerns of this patient population. Aspects of trust, respectful treatment and clear communication in healthcare encounters are particularly important to provide high-quality care to asylum seekers and should be strengthened.